PENGARUH ROA DER DAN PBV TERHADAP PER PADA PERUSAHAAN INVESTASI YANG TERDAFTAR DI BEI TAHUN 2014-2021 - Dhalia Vellati; Clarisa Listya Dewi; Nikmatus Sholehah; Sheila Amanda Widyadhari (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine the effect of Return On Assets (ROA), Debt to Equity Ratio (DER), and Price to Book Value (PBV) in Investment Companies Listed on the IDX 2014-2021. This study uses a quantitative data type method. Data analysis of the Classical Assumption Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, and Hypothesis Test assisted with the SPSS program. In taking the sample of this study using purposive sampling method. The samples obtained were 8 companies that met the criteria in this study and the research data collected were 64 data for 8 years. Based on the results of this study indicate that Return on Assets (ROA) has a positive and significant effect on the price earning ratio (PER). However, the Debt to Equity Ratio (DER) has a negative and insignificant effect on the Price Earning Ratio (PER). Meanwhile, the Price to Book Value (PBV) has a negative and significant effect on the Price Earning Ratio (PER).